Bagaimana Tingkat Kesejahteraan Masyarakat, Pendidikan, dan Layanan Kesehatan Berdampak terhadap Penyebaran Kasus Positif dan Kematian Covid-19 di Jawa Bali? - Syahindra, Muhammad Rizky (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
Many factors cause the distribution of positive cases and deaths of Covid-19 in Indonesia. This study aims to determine the effect of welfare, Education, and health services on positive cases and fatalities of COVID-19 from 128 regencies and municipalities in Java and Bali islands. Data were collected from BPS and kawalcovid19.id. This study applied the Ordinary Least Squared method in two models. The variables are converted into Natural Logarithmic. The results of the regression of Model I show a high determination coefficient value of 0.718 with the value of the Regional GDP income per capita of (-0.389), Regional GDP (0.739), and Education (2.139) affect the distribution of the positive cases of Covid-19, except variable of Poverty (0.045) whose results are not significant. Meanwhile, Model II shows a regression result of Positive Covid-19 cases (0.999), Regional GDP income per capita (1.052), Regional GDP (-0.955) can affect the death cases of Covid-19 (0.151), Education (0.-431), and Health (0.-165) with nonsignificant results. Moreover, in this Model, the independent variable can affect the spread of death cases of Covid-19 by 59.3%.